Co‐Creation in Research: Further Reflections From the ‘Co‐Creating Safe Spaces’ Project - Scott J. Fitzpatrick; Heather Lamb; Erin Oldman; Melanie Giugni; Cassandra Chakouch; Alyssa R. Morse; Amelia Gulliver; Erin Stewart; Stride Safe Space and Safe Haven Team; Helen T. Oni; Benn Miller; Bronwen Edwards; et al. (Health Expectations)
ABSTRACT Background Applied research using co‐creation methods is rarely described or evaluated in detail. Practical evidence of co‐creation processes and collaboration effectiveness is needed to better understand its complex and dynamic nature. Methods Using a case study design and survey method, we assessed processes of co‐implementation and co‐evaluation grounded in our own experiences from the Co‐Creating Safe Spaces project. We examine these in the context of a published systematic framework designed to improve clarity about co‐creation processes and report on how co‐creation was experienced by collaborative partners. Results Our study showed the interconnectedness between co‐implementation and co‐evaluation processes and the importance of aligning research with program processes to ensure it is responsive to emergent local needs and problems. Given relatively low levels of researcher embeddedness across sites, service champions played a pivotal role in data collection. Survey findings indicated strong support for a healthy collaboration with some concerns expressed over individual partner's areas of responsibility and ability to deliver on commitments. Conclusion Co‐creation can be a very robust approach to translational research but is a complex endeavour. Ongoing reflexivity and attention to relational aspects support genuine collaboration and provide a foundation for addressing challenges. Patient or Public Contribution People with lived experience of emotional distress and/or suicidal crisis, including researchers from both academic and non‐research backgrounds, service managers, peer workers, carers and advocates, were involved in this research and authored this paper.